Diseño del Sistema de Gestión de Calidad basado en la NTC ISO 15189:2022 para el Laboratorio Anatomía Patológica del Doctor Jairo Alberto Díaz Torres (2023)
The purpose of this research is to improve the quality of the service provided by the pathology anatomy laboratory of Doctor Jairo Alberto Diaz Torres through the design of the Quality Management System based on the ISO 15189:2022 standard, which leads to the standardization of processes. The research method used was descriptive and its approach will be mixed quantitative and qualitative; supported by instruments that allowed the assessment of the QMS, the checklist was used for verification based on the criteria of the standard and a survey of laboratory staff to collect the necessary information against the requirements of the standard, obtaining from the checklist the compliance of the initial diagnosis against the quality with a high percentage between 75%, then based on the results the required documentary structure was formulated to ensure standard compliance based on ISO 15189: 2022, obtaining a percentage of compliance against the technical and quality management requirements, the percentages will increase when implementing the Quality Management System to the Anatomic Pathology Laboratory. Keywords: NTC ISO 15189:2022, Quality Management System, Documentation, Process standardization.